S37 Vascular Endothelial Cell Growth Factor-a (vegf-a) Signalling And Neovascularisation Of Pulmonary Endarterectomy Material In Chronic Thromboembolic Pulmonary Hypertension (cteph). (10th November 2014) - Southwood, M; Hadinnapola, C; Moseley, E; Jenkins, D; Goddard, M; Sheares, K; Toshner, M; Pepke-Zaba, J
Abstract : Background: Despite recent advances in the medical treatment of patients with CTEPH, relatively little is understood surrounding the underlying pathological mechanisms. Many patients have a historical documented venous thromboembolic event (VTE) and consequently, failed resolution of an acute VTE has been proposed as a key initiating factor in the subsequent development of CTEPH. Here we investigated VEGF-A levels, a key regulator of angiogenesis, in CTEPH patients prior to and following pulmonary endarterectomy (PEA) surgery to remove the thromboembolic material. We also examined the surgically excised PEA material and measured neovessel density in distal regions of the specimens. Methods and results: Serum VEGF-A levels were measured by Luminex array in paired serum samples from n = 44 patients at baseline (before PEA surgery) and following PEA surgery. Following PEA surgery, serum VEGF-A levels were significantly reduced compared to baseline measurements (159.5 ± 174.8 vs. 194.4 ± 198.2, p = 0.0182). Distal regions of excised PEA material were cross sectioned and processed for histopathological examination. Neovessel density was calculated by counting the absolute number of vascular channels present within a cross-sectional area and normalised to tissue area using Image J. We also measured the time between documented VTE and subsequent PEA surgery (VTE-PEA time) in patients with a documented VTE (n = 40/44 [90%] patients), and identified an inverse correlation between neovessel density and VTE–PEA time. Conclusions: Extensive angiogenesis was evident in distal PEA material from patients with CTEPH. VEGF-A is known to be a key regulator of angiogenesis and serum levels were significantly reduced following PEA surgery. Interestingly, a significant inverse correlation between neovessel density and VTE-PEA time was observed indicating that in the early stages following VTE, extensive angiogenesis is evident within the thromboembolus. Taken together these data provide further evidence that angiogenesis is an important mechanism in the attempted resolution of a VTE.